DYSMENORRHEA AMONG FEMALE MEDICAL SCIENCES STUDENTS IN MACHS: PREVALENCE, PREDICTORS AND OUTCOME - KANNAN, LATHA S; EG, HASSAN; Lewis, Sharell; Sivapalan, Nisha; CASINGAL, BERNADETTE; RM, PALANIVEL (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This study intended to determine the prevalence, predictors, and outcome of dysmenorrhea among female medical sciences students at Mohammed Al-Mana College for Medical Sciences (MACHS), Dammam, Saudi Arabia. Methods: A cross-sectional study was adopted, and 292 female medical sciences students of MACHS were selected using stratified random sampling. A semi-structured and self- administrated questionnaire was used to collect personal and socio-demographic information from the selected female medical sciences students. The information about the menstrual history, stress, and smoking were also gathered. The data analysis was carried out using the descriptive statistics and Chi-square test. Results: The prevalence of dysmenorrhea was 73.28% among female medical sciences students. Concerning the signs and symptoms of dysmenorrhea, the abdominal pain was predominant symptoms among 73.28% of the respondents, and it was found to be statistically significant (p≤0.05). Sleep disturbance was observed as the prominent outcome of dysmenorrhea, as reported by 64% of the respondents.